Quantification of end-of-life tyres in West Africa—developing a region-wide estimation framework - Narra, Mona-Maria; Agboka, Komi; Narra, Satyanarayana; Nelles, Michael (Frontiers in Sustainability, 2025)
End-of-life tyres (ELTs) represent a significant environmental and public health challenge across West Africa, yet fundamental data on ELT generation rates remain largely unavailable for most countries in the region. This study addresses this critical knowledge gap by developing and applying a comprehensive framework to quantify ELT generation across the 16 West African countries. Through systematic literature review and bottom-up estimation modelling, the current state of ELT data availability and developed region-specific generation estimates were assessed. Using a parametric calculation model that integrates vehicle fleet size, composition, tyre specifications, and replacement frequencies calibrated for West African conditions, ELT generation for 11 countries was quantified. The literature review revealed profound data scarcity, with only 5 out of 16 countries (31%) having any available ELT generation data, ranging from 8,000 tonnes annually in Burkina Faso to 2.5 million tonnes in Nigeria. ELT generation totaling approximately 840,000 tonnes annually was quantified. Nigeria dominates regional ELT generation with 646,288 tonnes per year (77% of quantifiable regional total), followed by Senegal (57,936 tonnes) and Ghana (46,031 tonnes). Vehicle fleet compositions vary significantly across the region, with some countries showing motorcycle-dominant fleets (up to 83% in Burkina Faso) while others are car-dominant (50–67% in most countries). The study reveals substantial methodological challenges, including temporal inconsistencies in available data (spanning 2007–2020), varying institutional data sources, and complete data absence for several countries including Mauritania, Côte d’Ivoire, Guinea-Bissau, and The Gambia. This diversity has important implications for waste stream characteristics and recycling infrastructure requirements. These limitations highlight the urgent need for standardised ELT monitoring systems across the region. The findings demonstrate that ELT generation patterns reflect complex interactions between population size, economic activity, and transportation infrastructure rather than simply following GDP per capita distributions. The concentration of waste generation in a few countries suggests opportunities for regional cooperation in developing processing infrastructure, while the manageable scale in most countries (below 60,000 tonnes annually) indicates potential for cross-border collaborations. This research provides the first comprehensive regional assessment of ELT generation in West Africa and establishes a replicable methodology for ongoing monitoring. The results support evidence-based policy development, infrastructure planning, and regional cooperation strategies for sustainable ELT management across West Africa.